1997
DOI: 10.1038/bjc.1997.283
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-2 oncoprotein detected by automated quantitative immunocytochemistry in breast carcinomas correlates with patients' overall and disease-free survival

Abstract: Summary The prognostic significance of c-erbB-2 oncoprotein overexpression detected in tumours by immunocytochemical assays (ICAs) was investigated in 148 breast carcinomas. ICAs were performed under optimal technical conditions with frozen tissue sections and included automated immunoperoxidase technique and computer-assisted analysis (densitometry) of digitized coloured microscopic images. Results of quantitative ICAs (expressed in percentages of c-erbB-2-positive surfaces and mean optical densities) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Epidermal growth factor receptor overexpression was always associated with poor outcome, manifested in a short overall survival and disease-free interval (Sainsbury et al, 1985;Lewis et al, 1990;Toi et al, 1994;Tsutsui et al, 2002), high metastatic potential (Sainsbury et al, 1987) and negative oestrogen receptor (ER) status (Pilichowska et al, 1997;Tsutsui et al, 2002). The same behaviour was also detected in tumours showing c-erbB-2 gene amplification and/or overexpression, which was marked in high tumour grade as well as short overall survival and disease-free interval (Winstanley et al, 1991;Charpin et al, 1997;Suo et al, 2002).…”
mentioning
confidence: 78%
“…Epidermal growth factor receptor overexpression was always associated with poor outcome, manifested in a short overall survival and disease-free interval (Sainsbury et al, 1985;Lewis et al, 1990;Toi et al, 1994;Tsutsui et al, 2002), high metastatic potential (Sainsbury et al, 1987) and negative oestrogen receptor (ER) status (Pilichowska et al, 1997;Tsutsui et al, 2002). The same behaviour was also detected in tumours showing c-erbB-2 gene amplification and/or overexpression, which was marked in high tumour grade as well as short overall survival and disease-free interval (Winstanley et al, 1991;Charpin et al, 1997;Suo et al, 2002).…”
mentioning
confidence: 78%
“…In addition to Southern and slot-blotting techniques to evaluate HER2 status in breast cancer, polymerase chain reaction (PCR) methods, and more recently, in situ hybridization (Ross and Fletcher, 1999) have been used. Qualitative and quantitative HER2 protein measurements have been obtained using immunohistochemistry (Allred et al, 1992;Battifora et al, 1991;Berger et al, 1988;Bianchi et al, 1993;Charpin et al, 1997;Dykens et al, 1991;Fernandez et al, 1997;Gusterson et al, 1992;Hartmann et al, 1994;Hieken et al, 1996;Jacquemier et al, 1994;Kallioniemi et al, 1991;Lovekin et al, 1991;Marks et al, 1994;McCann et al, 1991;Molina et al, 1992;Muss et al, 1994;Noguchi et al, 1992;O'Malley et al, 1996;O'Reilly et al, 1991;Paik et al, 1990;Press et al, 1993;Quenel et al, 1995;Rilke et al, 1991;Rosen et al, 1995;Sundblad et al, 1996;Tetu and Brisson 1994;Van de Vijver et al, 1988;Winstanley et al, 1991) on frozen and archival tissues, and Western blotting (Giai et al, 1994;Molina et al, 1992), and enzyme immunoassays Eissa et al, 1997;Hieken et al, 1996) on solubilized tumor extracts. Northern blot has been used to measure the level of specific mRNA (Gia...…”
Section: Her2 Amplification and Overexpression: Prognostic Valuementioning
confidence: 99%
“…Nor did we see an influence related to tumor size in these patients. Several previous studies have reported associations of positive HER‐2 status with poor prognosis for node‐negative disease (19–21), particularly a study that reported greater precision in the prognostic estimate when considering the size of the tumor (9).…”
Section: Discussionmentioning
confidence: 99%